efectuati calculele va rog ajutați ma

Răspuns:
Explicație pas cu pas:
a)(9/2√6-4/3√6-2/√6)-(12/3√54-18/√54)
√54=3√6
=1/√6(9/2-4/3-2)-(4/3√6-6/√6)=1/√6(27-8-12)/6-1/√6(4/3-6)=
=7/6√6-1/√6·(4-18)/3=7/6√6+14/3√6=7/3√6(1/2+2)=7·3/3·√6
=7/√6=7√6/6
b)(9/√6-8√6-6/√6)-(8/5√6-12/5√6)-(3/√6-4/√6)=
=1/√6(9-8-6)+4/5√6+1/√6=-5/√6+4/5√6+1/√6=-4/√6+4/5√6=
=4/√6(-1+1/2)=-2/√6=-√6/3
c)1/√2(2/3+5/2)-(3√2/2-1/3√2)=1/√2·19/6-(18-2)/6√2=19/6√2+16/6√2=
=1/6√2(19+16)=35/6√2=35√6/12
d)(4/5√2+3/2√2)-(5√2/4-3/√2)=1/√2(4/5+3/2)-(5·2-12)/4√2=
=23/10√2+2/4√2=23/10√2+1/2√2=1/2√2(23/5+1)=1/2√2·28/5
=14/5√2=7√2/5